If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
13*x-17 = 3*x-(56/8) // - 3*x-(56/8)
13*x-(3*x)+56/8-17 = 0
13*x-3*x+56/8-17 = 0
10*x-10 = 0 // + 10
10*x = 10 // : 10
x = 10/10
x = 1
x = 1
| X^2-9y^2+z^2=0 | | (6/x)+(1/7)=(5/3x) | | 6/x+1/7=5/3x | | 1=6x-15y | | 1,7x+11000=25000 | | 9/4-1/2 | | 1,20x+12000=25000 | | -4x-y=6 | | 0,95x+16000=25000 | | 12-4x+8=5+6x+5 | | 9/140+0.1 | | 4*(-2x-5)-8*(8-3x)=4*(7-4x) | | 5*(3x+7)+2*(2x-6)=3*(4-5x)-23 | | 6*(x-2)-4*(x-3)=4*(x+4)-(x-10) | | 1=9x+25 | | 6x2y/2y | | 3*(3x+7)=5*(3x+8)-2*(4x-17) | | 7x+3*(2x-1)=4*(2x+1)+3 | | 3x-(1/2)*((x/5)+6)=25+(3x/2) | | (p-3)/4-1+2 | | 9*(7x-5)+11*(4x+9)=17*(6x-3) | | x^3+6x^2+5x=12 | | 3x-(1/2)((X/5)+6)=25+(3x/2) | | 6(y+7)-8y=26 | | 0,7x+0,5=10 | | 7-(2x-3)+x=x-1-3(2x+1) | | x^2+7=4x | | (2x+1)-3(5x+1)=2(x-4)-(3x-6) | | 265000*x^8=100000 | | 3x*33-2*3x=2x+3 | | 3x*33-2*3x= | | 6(3-9x)=90-42x |